A case of humidifier lung with a difficult differential diagnosis from COVID-19. Issue 10 (26th October 2021) - Ono, Mariko; Nagatomo, Yoko; Kinoshita, Hayato; Takeda, Yukihisa; Nakamura, Hiroyuki; Aoshiba, Kazutetsu
ABSTRACT: Acute respiratory illnesses that presented with diffuse ground-glass opacities (GGOs) on chest computed tomography (CT) scan suggest the diagnosis of coronavirus disease 2019 (COVID-19). However, many other diseases show similar CT findings, which often offer a difficult differential diagnosis. Here, we report a case of humidifier lung, a rare phenotype of hypersensitivity pneumonitis (HP), which mimicked COVID-19. A 71-year-old man was admitted because of dyspnea and diffuse GGOs found on chest CT scan. Although COVID-19 was initially suspected, his symptoms rapidly improved by the next day. A medical interview revealed that he had started using an ultrasonic humidifier 1 month ago. A high-resolution CT (HRCT) scan showed ill-defined centrilobular nodules and mosaic attenuation, which are typical of HP but atypical of COVID-19. The inhalation challenge test confirmed the diagnosis of humidifier lung. History-taking of humidifier use and a precise HRCT interpretation are helpful to differentiate it from COVID-19.